2021
DOI: 10.1097/cce.0000000000000373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Patients With Sepsis Discharge Diagnosis Codes and Short Lengths of Stay in U.S. Hospitals

Abstract: Objectives: Some patients diagnosed with sepsis have very brief hospitalizations. Understanding the prevalence and clinical characteristics of these patients may provide insight into how sepsis diagnoses are being applied as well as the breadth of illnesses encompassed by current sepsis definitions. Design: Retrospective observational study. Setting: One-hundred ten U.S. hospitals in the Cerner HealthFacts dataset (primary cohort) and four ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The mortality of patients with sepsis is also positively correlated with age [32]. Therefore, it is clinically feasible to use the comorbidity index to determine the risk of mortality of patients with sepsis, consistent with other studies [33][34][35].…”
Section: Discussionsupporting
confidence: 83%
“…The mortality of patients with sepsis is also positively correlated with age [32]. Therefore, it is clinically feasible to use the comorbidity index to determine the risk of mortality of patients with sepsis, consistent with other studies [33][34][35].…”
Section: Discussionsupporting
confidence: 83%
“…4 Another study reported that, among 67 733 patients with sepsis diagnosis who were admitted to 110 US hospitals, 1 in 10 were discharged alive within 3 days. 5 The analysis by Peltan and colleagues 3 expands on these studies by providing the clinical characteristics and 30-day outcomes of patients with sepsis who were discharged from the ED.…”
Section: Similar Observations Have Previously Been Reported a Nationa...mentioning
confidence: 99%
“…4 Another study reported that, among 67 733 patients with sepsis diagnosis who were admitted to 110 US hospitals, 1 in 10 were discharged alive within 3 days. 5 The analysis by Peltan and colleagues 3 expands on these studies by providing the clinical characteristics and 30-day outcomes of patients with sepsis who were discharged from the ED.These patients tended to be younger and less severely ill compared with those who were admitted to the hospital, with fewer perturbations in their vital signs, milder organ dysfunction, and higher rates of arrival by private vehicle over ambulance. Two-thirds had urinary infections, whereas those who were admitted to the hospital more commonly had pulmonary or intra-abdominal infections.The 30-day mortality rate in patients who were discharged was only 0.9% compared with 8.3% in those who were hospitalized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, I also believe they can inadvertently promote cognitive biases such as diagnostic anchoring and premature closure, thereby preempting consideration of alternate diagnoses. Proof of the negative impact of these diagnostic aids may be hard to come by, but many have expressed this concern . Furthermore, these diagnostic aids may pose a particular concern about their effect on the development of medical trainees’ clinical reasoning skills.…”
mentioning
confidence: 99%